2001
DOI: 10.1023/a:1015615130459
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Firstly, in this population the response rate (83.6%) in the original study was high enough to provide reliable results for respiratory symptoms and diseases, only the prevalence of current smoking was biased by non-response. Secondly, the methods used for collecting responses in a non-response study may influence the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 19 publications
6
29
1
Order By: Relevance
“…Results from the present study indicated that long-term participants had less respiratory symptoms compared to all baseline participants in RHINE, ISAYA and I-ECRHS, with the exception of rhinitis. In the literature, we find studies that are both in accordance and in discordance with our results [14,15,22,25,28-30]. These differences between studies show the importance of assessing selection bias in every longitudinal study, rather than simply stating the response rate [26,31].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Results from the present study indicated that long-term participants had less respiratory symptoms compared to all baseline participants in RHINE, ISAYA and I-ECRHS, with the exception of rhinitis. In the literature, we find studies that are both in accordance and in discordance with our results [14,15,22,25,28-30]. These differences between studies show the importance of assessing selection bias in every longitudinal study, rather than simply stating the response rate [26,31].…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have furthermore shown that non-responders tend to be smokers to a larger degree than responders [22,25-28]. At the baseline studies in RHINE and I-ECRHS, we did not have information on smoking habits among responders and non-responders, but a previous report from ISAYA showed that smokers were over-represented among late responders compared to early responders [15].…”
Section: Discussionmentioning
confidence: 93%
“…Attempts to study whether and how the decreasing participation rates affect the results have been made in studies on respiratory epidemiology [25,26,4145], and the results all seem to indicate that non-participants typically are male, smokers, and younger subjects [26,44,45]. It can be reasonably assumed that prevalence estimates may be more affected by increasing non-participation than associations between a risk factor and an outcome [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the demographic characteristics and survey results of responders are not equivalent to those of nonresponders. 30 Unfortunately, demographic data were not collected during registration, so we were unable to compare responders and nonresponders. This represents a serious limitation to this study and merits consideration in conducting future group-consensus studies.…”
Section: Discussionmentioning
confidence: 99%